A GIS Based Approach to Manage Spatial Distribution and Location of Financial Services: A Case Study of ATM Services - Khan, Md Sadat; Yesmin, Nurshad (Journal of Bangladesh Institute of Planners, 2016)
Location convenience is an important factor when customers select a financial institution. To stay competitive, banks usually attempt to increase convenience (be as close as possible to customers) by expanding their branch or ATM networks. Using GIS in the arena of finance can be very supportive and cost effective to facilitate location based decisions for financial institutions. For business expansion planning, banks need location-relevant data, and cost effective site analysis to select a new bank branch or ATM location confidently and reliably in a shorten-time cycle. When banks plan to open new branches, they need to consider the data such as the concentration of commercial areas, traffic patterns, workplaces or living places of customers whose demographics and purchase behavior match banks’ target customer profiles. In this research, GIS-based approach has been developed to identify suitable location for an ATM network in Perspective of Bangladesh. The newly established banks those have not set up ATM network yet or have very small scale ATM services network can expand their banking services through acquiring partners from existing ATM network of other Banks and simultaneously can construct new ATMs in the most suitable unserved areas. This is how these banks can expand their ATM network more rapidly with a less establishment cost. Also banks, those have large ATM network with some unserved areas, can expand their existing network by reaching to the customers’ convenience locations. The paper recommends that the analysis using GIS to find most suitable locations for ATM is better applicable for other cities and towns. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 125-140